A STUDY OF PARTICULATE AND GASE-OUS EMISSIONS OF A DAMAGED TUBU-LAR COMBUSTION CHAMBER IN A PELLET STOVE - Praunseis, Zdravko (Journal of Energy Technology, 2023)
Wood-burning boilers are a popular source of heating in Slovenia. However, there has been much de-bate about the potential negative health effects associated with wood smoke in recent years. Woodsmoke is increasingly seen as a significant component of airborne particulate matter (PM), especially in the context of the new sort time standard for fine particles in ambient air. Most organic substances will be burnt in the boilers during good combustion conditions with sufficient oxygen supply and high temperature. This study presents the influence of damaged tubular combustion chamber on smoke fine-particle emissions at small scale pellet burners. This research aims to reduce the particulate matter emissions of small scale pellet boilers and contribute to cleaner air.